Coping with the Cold : Heating Strategies for Eastern Europe and Central Asia's Urban Poor - Lampietti, Julian A.; Meyer, Anke S. (Washington, DC: World Bank, 2013)
Heating is a critical issue for the livelihoods of Eastern Europe and Central Asia's people. The region's gold climate, the legacy of central planning, and the drop in household incomes over the past 10 years, influence profoundly the design of heating strategies for the urban poor. This paper provides new insights into how much energy people demand for heating, and how much they pay for it. Recommendations are suggested on how to design policies, and investment planning, that would enable all people (poor and non-poor) to access clean, affordable heating.